A Study on Awareness of Central Government Schemes for the Sustainable Development of Rural India with Reference to Coimbatore - Dr. D. Moorthy; Christina Jeyadevi J (International Journal of Engineering and Management Research, 2023)
The government of India has introduced many schemes for the development and upliftment of the rural people in India. The schemes were introduced to develop rural, underprivileged youth into a self-sufficient, employable workforce and to convert the rural population into a self-sustained generation with housing and income generation. Since it was introduced through banks and financial organizations, people in the banks and people who have knowledge about banks and loans alone were able to get the benefits of the schemes. To implement the schemes, the government of India has started programs through schools and colleges. The following are the objectives of the study. (i) to present the various central Government Schemes of Rural India, (ii) to present the socio-economic profile of the sample respondents, (iii) to study the level of awareness about the central government schemes and (iv) to give suggestions to create more awareness about the central government scheme for rural India. Though many schemes are available and many are developed in many parts of the country, people in the South are not aware of these schemes available for them. So, an attempt has been made to know the awareness of the Central Government Schemes available, the researchers had taken 238 random sample respondents in the city of Coimbatore. The results showed that the people had a medium level of awareness of the Central Government Schemes and suggestions were given accordingly.